Effect of chitosan from crab shells (Portunus pelagicus) on the chemical properties of liquid fertilizer - Putri, Try Amelia; Harianti, Harianti; Basir, Buana; Khairiyah, Zul (Sangia Research Media and Publishing, 2025)
Swimming crab shell waste is a fishery byproduct that has the potential to pollute the environment if not utilized properly. One alternative utilization is to process it into chitosan, which is then formulated into liquid fertilizer. This study aimed to determine the effect of chitosan concentration based on swimming crab shells on the chemical properties of liquid fertilizer. The study was conducted from February to March 2025. Chitosan and liquid fertilizer production was conducted at the Fishery Products Biochemistry Laboratory, Pangkep State Agricultural Polytechnic. The method used was an experimental laboratory with a Completely Randomized Design (CRD), with three treatments and three replications, with chitosan concentrations of 2%, 4%, and 6%. Data were analyzed using One-Way ANOVA and the W-Tukey HSD test. If the assumption of homogeneity of variance was not met, Welch ANOVA with the Games-Howell test was used to determine differences in effects between treatments. The results showed that the treatment had a significant effect (P<0.05) on most of the chemical properties of liquid fertilizer. The chemical properties of pH were (2.90 3.00 3.23), C-organic were (1.08% 2.72% 4.21%), macronutrients N + P2O5 + K2O were (0.76% 0.64% 1.19%). In conclusion, increasing the concentration of chitosan improves the chemical properties of liquid fertilizer, so that crab shell chitosan has the potential as a material for liquid organic fertilizer formulation.